2022
DOI: 10.1021/acsearthspacechem.2c00009
|View full text |Cite
|
Sign up to set email alerts
|

Rare-Earth Elements and Heavy Metals in Atmospheric Particulate Matter in an Urban Area

Abstract: Atmospheric particulate matter (PM10), one of the criteria air pollutants, significantly impacts human health and the climate. To enhance our fundamental understanding of atmospheric PM10 characteristics, rare-earth elements (REEs) and heavy metals were evaluated along with their source apportionment using the positive matrix factorization (PMF) model. The PM10 mass concentration and elemental (REEs and heavy metals) compositions were analyzed using the gravimetric and HR-ICPMS methods. Although the PM10 conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 67 publications
2
7
0
Order By: Relevance
“…The mean concentrations of PM 2.5 were recorded low in 2020 and 2021 due to restricted activities during the Covid-19 lockdown period of S (2.29 ± 1.61 µg m − 3 ), Cl (2.26 ± 2.50 µg m − 3 ), K (2.05 ± 1.83 µg m − 3 ), Ca (0.96 ± 1.17 µg m − 3 ) and Fe (0.93 ± 0.58 µg m − 3 ) were recorded in all the samples of PM 2.5 during the entire study period followed by Zn (0.62 µg m − 3 ) > Pb (0.57 µg m − 3 ) > Al (0.51 µg m − 3 ) > Na (0.35 µg m − 3 ) > Cu (0.29 µg m − 3 ) > Ti (0.27 µg m − 3 ) > As (0.26 µg m − 3 ) > Cr (0.24 µg m − 3 ) > Mo (0.19 µg m − 3 ) > Br (0.16 µg m − 3 ) > Mg (0.14 µg m − 3 ) > Ni (0.14 µg m − 3 ) > Mn (0.12 µg m − 3 ) > and P (0.08 µg m − 3 ). The presence of Al, Fe, Na, Mg, Ca, S, Cl and K as major elements in PM 2.5 is also supported by other studies conducted in Delhi (Jain et al 2017;Rai et al 2020;Bangar et al 2021) and other locations of India (Sharma et al 2020(Sharma et al , 2022Choudhary et al 2020;Rabha et al 2022). Hazarika et al (2015) also reported the abundance of Na, Ca, Mg, Si and K in PM 2.5 samples followed by Ni, Cu and Pb in urban site of Delhi.…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…The mean concentrations of PM 2.5 were recorded low in 2020 and 2021 due to restricted activities during the Covid-19 lockdown period of S (2.29 ± 1.61 µg m − 3 ), Cl (2.26 ± 2.50 µg m − 3 ), K (2.05 ± 1.83 µg m − 3 ), Ca (0.96 ± 1.17 µg m − 3 ) and Fe (0.93 ± 0.58 µg m − 3 ) were recorded in all the samples of PM 2.5 during the entire study period followed by Zn (0.62 µg m − 3 ) > Pb (0.57 µg m − 3 ) > Al (0.51 µg m − 3 ) > Na (0.35 µg m − 3 ) > Cu (0.29 µg m − 3 ) > Ti (0.27 µg m − 3 ) > As (0.26 µg m − 3 ) > Cr (0.24 µg m − 3 ) > Mo (0.19 µg m − 3 ) > Br (0.16 µg m − 3 ) > Mg (0.14 µg m − 3 ) > Ni (0.14 µg m − 3 ) > Mn (0.12 µg m − 3 ) > and P (0.08 µg m − 3 ). The presence of Al, Fe, Na, Mg, Ca, S, Cl and K as major elements in PM 2.5 is also supported by other studies conducted in Delhi (Jain et al 2017;Rai et al 2020;Bangar et al 2021) and other locations of India (Sharma et al 2020(Sharma et al , 2022Choudhary et al 2020;Rabha et al 2022). Hazarika et al (2015) also reported the abundance of Na, Ca, Mg, Si and K in PM 2.5 samples followed by Ni, Cu and Pb in urban site of Delhi.…”
Section: Methodssupporting
confidence: 71%
“…associated with PM 2.5 in the urban area is mainly from crustal/soil/road dust, combustion of biomass and fossil fuel, emissions from vehicles and industrial activities (Sharma and Mandal 2017;Rai et al 2020;Bangar et al 2021;. Several studies have been conducted on chemical characteristics (organics, soluble ions & organics, elements) and source apportionment of PM in India (Choudhury et al 2022;Kumar and Sarin 2009;Mandal et al 2014;Sharma et al 2018;Kaushal et al 2018;Begam et al 2017), but a few studies have been carried out on elemental concentration and their sources (Rai et al 2020;Bangar et al 2021;Rabha et al 2022). In this manuscript, we report the seasonal and annual elemental composition (Ti, Cu, Zn, Mn, Al, Fe, Cr, Ni, Mo, Na, Mg, Ca, Cl, P, S, K, Pb, As, and Br) of PM 2.5 in Delhi, India based on long-term observations (January, 2017to December, 2021.…”
mentioning
confidence: 99%
“…These metals were typical industrial-emission elements. Cd had the highest enrichment factor, which indicated that it was affected by extremely severe human activities (Rai et al, 2020;Rabha et al, 2022). At the same time, relevant studies have shown that metal processing and the chemical industry were an important contributor for Cd (Qing et al, 2007;Yang et al, 2016;Othman et al, 2019;Wu et al, 2021).…”
Section: Source Identificationmentioning
confidence: 99%
“…Rai et al (2020) qualified the 26 elements in airborne particles in Delhi and identified the nine different sources of elements in PM 2.5/10 by using PMF. Rabha et al (2022) used PMF for source apportionment which reveals the contributions of five significant sources of PM 10 mass in the urban area of Jorhat, which found that coal combustion and vehicular emission followed by biomass burning, soil dust, and industrial emission were the main sources. To improve the precision, the application of different multivariate receptor models to source apportionment has been a hot topic in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, because of their widespread application in high-tech manufacturing industries worldwide as well as in agriculture and of the subsequent release into soil, water, and atmosphere, the risk of uncontrolled human exposure to REEs is progressively growing [ 8 ]. Among others, contamination of water bodies by rare-earth elements is a particularly hot issue since ingestion of contaminated aquatic foods and drinking water are primary pathways for human exposure to REEs and an increasing body of literature has reported, from time to time, anthropogenic rare-earth elements in aquatic systems in various countries [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%